Perceptions and Experiences of Older Persons in Two Types of Institution in France: Foster Care Family Institution and Medico-Social One - Chammem, Rita; Domi, Serge; Schott, Anne Marie (Frontiers in Public Health, 2021)
Background: The rapid increase in the number of older people with loss of autonomy and requiring human support, medical services, and adapted accommodation is a challenge in many countries. Beside institutions for older people, foster care families may offer an interesting innovative and affordable alternative that should to be evaluated. As the place of living has a major impact on the quality of life, our objective was to compare the perceptions and experience of older adults depending on the type of accommodation in which they live in. Methods: This study was based on a mixed method approach, with a quantitative assessment and a qualitative study with semi-structured interviews conducted with older people living in two different types of institutions: medico-social institution and foster care families. We explored the perceptions and the quality of life of the participants. Results: Institutionalization, chosen or not, can represent a trauma for older people as it disrupts their personal habits. Participants described medico-social institutions as an institutional framework supported by a strict professional team and rules, as impersonal structures (i.e., somewhat neutral), and as offering a very present, prepared, and respected reception protocol on the first day of arrival, which remained marked in memories. On the other hand, foster care families were considered as more spontaneous and family-oriented structures relying on internal and negotiable rules, offering personalized and close support in the face of loss of autonomy, but in which the reception protocol on the first day of arrival was almost absent. Conclusions: Foster care families and medico-social institutions presented different advantages and disadvantages from the point of view of the participants. This can help health policy makers to rethink the way seniors are housed by taking into consideration their perception and quality of life.